2011
DOI: 10.3109/00498254.2011.611546
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species absorption, metabolism, distribution and pharmacokinetics of BI 201335, a potent HCV genotype 1 NS3/4A protease inhibitor

Abstract: The present study describes the cross-species absorption, metabolism, distribution and pharmacokinetics of BI 201335, a potent HCV protease inhibitor currently in phase III clinical trials. BI 201335 showed a good Caco-II permeability (8.7 × 10(-6) cm/sec) and in vitro metabolic stability (predicted hepatic clearence (CL(hep)) <19% Q(h) in all species tested). Single dose PK revealed a clearance of 17, 3.0 and 2.6 mL/min/kg in rat, monkey and dog respectively, with a corresponding oral bioavailability of 29.1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Faldaprevir is a low-clearance drug that is metabolically very stable in vitro (Duan et al, 2012). However, the human ADME study revealed two abundant monohydroxylated metabolites, M2a and M2b, excreted in feces, accounting for ;40% of the dose, but not found in human plasma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faldaprevir is a low-clearance drug that is metabolically very stable in vitro (Duan et al, 2012). However, the human ADME study revealed two abundant monohydroxylated metabolites, M2a and M2b, excreted in feces, accounting for ;40% of the dose, but not found in human plasma .…”
Section: Discussionmentioning
confidence: 99%
“…Faldaprevir is a low-clearance drug in humans (Duan et al, 2012) that predominantly undergoes oxidation to form two abundant hydroxylated metabolites (M2a and M2b) detected in feces at ;40% of the administered dose without exhibiting appreciable levels of circulating metabolites . To effectively investigate the interplay of faldaprevir with transporters and DMEs, it was important to select a cellular system in which sufficient levels of metabolites would be generated for this slowly metabolized drug.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocyte and incubation medium concentrations of tested compounds were determined against a corresponding standard curve by HPLC or LC-MS-MS as described in detail in a previous publication (10). Selection of bioanalysis methods was based on compound properties, and the best experimental condition was chosen to obtain analysis precision and accuracy (coefficient of variation [CV] Ͻ 12%).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected at 0, 0.25, 0.5, 1, 1.5, 2, 3, 4, 6, and 8 h postdosing, and plasma samples from 3 animals were pooled at each time point. All animal PK data were analyzed based on the standard noncompartmental model using WinNonlin (version 3.1; Scientific Consulting, Inc., Cary, NC) as described in a previous publication (10).…”
Section: Methodsmentioning
confidence: 99%
“…The cell pellet and medium samples were extracted with 2Â volume of acetonitrile containing 2% formic acid and centrifuged at 16,000g for 5 minutes. Levels of faldaprevir in the medium and cell pellet were determined by LC-MS, as described previously (Duan et al, 2012b).…”
Section: Uptake Into Suspended Hepatocytesmentioning
confidence: 99%